Dialektischer Negativismus: Michael Theunissen zum 60. Geburtstag - Angehrn, Emil; Pannenberg, Wolfhart; Figal, Günter; Schmitt, Carl (Suhrkamp, 1992)
"Dialektischer Negativismus". Michael Theunissen zum 60. Geburtstag. Herausgegeben von Emil Angehrn, Hinrich Fink-Eitel, Christian Iber und Georg Lohmann. Suhrkamp Verlag, Frankfurt am Main 1992. 380 S., br., 26,- DM
Bibliogr. M. Theunissen S. 372 - 376
Keywords: Theunissen, Michael -- 1932-2015; Bibliografie; Aufsatzsammlung; Festschrift; Geschichte; Philosophie; Theunissen, Michael